The Importance of the Rescue and Preservation of Medicinal Plants in the North region in the last twenty years - Lima, Renato Abreu; Xavier, Reinato Andrade Tembo; Cavalcante, Felipe Sant' Anna (Ciência e Natura, 2022)
The objective of this research was to survey published works on medicinal plants in the North Region, analyzing their use and preparation. Given its importance for human beings as well as for other living beings, the preservation of this precious asset on our planet Earth is very pertinent. The method for this study was quantitative, based on works published in the period from 1999 to 2019 with an emphasis on medicinal plants used in the treatment and cure of diseases. Visits to the communities, in the work under study, were analyzed for consultations in the region in order to improve capacities and data on medicinal plants. We found that the most used vegetable species were Lamiaceae, Asteraceae, Fabaceae, Rutaceae, Poaceae, Acanthaceae, Allismataceae, Amarantaceae, Anacardiaceae, Annonaceae, Meliaceae, Musaceae, Myrtaceae, Lauraceae, Malvaceae, Bromeliaceae, Cactaceae, Araceae, Apiaceae, Apocynaceae, Aristolochiaceae and others. Other records were people planting medicinal plants, collecting plant seeds, are used to make infusions to treat toothache, cough, flu, diarrhea and skin diseases.